PERFORMA ITIK LOKAL JANTAN (Anas plathyrynchos) YANG DIBERI PAKAN SUPLEMEN - Wara Pratitis Sabar Suprayogi; Sudibya Sudibya; Eko Hari Susilo (Universitas Sebelas Maret, 2017)
The research was to know the influence of the supplementation lemuru fish oil and L-carnitine on the local male ducks’ performance. The cattle used were 96 local male ducks aged 10 days. Research materials were corn, bran, concentrate 144, lemuru fish oil, and L-carnitine. The research design used was Complete Random Design with 3 treatments and 8 repetitions; each repetition contained 4 local male ducks. The treatment consisted of ration control P0 = corn, barn, concentrate and mineral; P1 = corn, barn, mineral and 4% lemuru fish oil; P2 = corn, barn, concentrate, mineral, 4% lemuru fish oil and 30 ppm L-carnitine. The investigated modifiers were feed consumption, feed conversion, daily weight increase and Income Over Feed Cost value. Data feed consumption, daily weight increase, feed conversion was analyzed using variance analysis. If there were a concrete influence, further analysis should be conducted using orthogonal contrast. Results showed that the supplementation of lemuru fish oil and L-carnitine had a very significant influence (P<0.01) on feed consumption, daily weight increase and feed conversion. Further test results orthogonal contrast showed that the supplementation of lemuru fish oil and L-carnitine could decrease feed consumption, feed conversion and increase daily weight rate (P<0.01) if compared control. Result Income Over Feed Cost showed that treatment with add lemuru fish oil and L-carnitine produced Income Over Feed Cost value higher if compared control. Based on the results of the research, it could be concluded that the supplementation of 4% lemuru fish oil and 30 ppm L-carnitine in ration could decrease feed consumption and feed conversion, increase daily weight rate, and the IOFC of local male ducks.